1984
DOI: 10.1080/00332747.1984.11024246
|View full text |Cite
|
Sign up to set email alerts
|

Broken Dreams: A Study of the Effects of Divorce and Depression on Dream Content

Abstract: To investigate the dream characteristics associated with a major life change, 29 women (ages 30-55) undergoing divorce were studied six nights in a sleep laboratory. The group was stratified on a self-report depression scale (the Beck Depression Inventory) into a depressed (N = 19, mean = 23.2) and nondepressed (N = 10, mean = 8.2) group and compared to a nondepressed married group who had never considered divorce. The dreams of those divorcing without major mood upset were longer and dealt with a wider time f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
53
0

Year Published

1990
1990
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(58 citation statements)
references
References 12 publications
5
53
0
Order By: Relevance
“…This proposal is compatible with psychological models suggesting that dreaming is a process of internal activation, arising from a person's affective and emotional history and serving an emotion-regulation function (e.g. Cartwright, Lloyd, Knight, & Trenholme, 1984;Cartwright, Luten, Young, Mercer, & Bears, 1998;e.g. Mancia, 2005;Nielsen & Levin, 2007).…”
Section: Functions Of Dreamingsupporting
confidence: 85%
“…This proposal is compatible with psychological models suggesting that dreaming is a process of internal activation, arising from a person's affective and emotional history and serving an emotion-regulation function (e.g. Cartwright, Lloyd, Knight, & Trenholme, 1984;Cartwright, Luten, Young, Mercer, & Bears, 1998;e.g. Mancia, 2005;Nielsen & Levin, 2007).…”
Section: Functions Of Dreamingsupporting
confidence: 85%
“…Breger, 1967;Koulack, 1993;Piccioni et al, 2002;Wright & Koulack, 1987). For example, dreams are very clearly affected by traumatic experiences (see reviews by, for example, Barrett (1996) and Punamäki (2007)), and other more common stressful waking-life experiences such as surgery (Breger, Hunter, & Lane, 1971) and divorce (Cartwright, 1991(Cartwright, , 2011Cartwright et al, 1984;Cartwright et al, 2001;Cartwright et al, 2006). However, while some experimental studies have found measurable effects of stressful experiences on dreams, mostly in terms of dream affect (de Koninck & Brunette, 1991;de Koninck & Koulack, 1975;Koulack et al, 1985), a naturalistic study found no effect either in terms of direct or indirect incorporations, or changes to dream affect (Delorme et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, it was surprising that stressfulness was not also found to be a factor, since some research has illustrated that experiencing stressful situations leads to dreaming of those situations, such as surgery (Breger, Hunter, & Lane, 1971) and divorce (Cartwright, 1991(Cartwright, , 2011Cartwright et al, 1984;Cartwright et al, 2001;Cartwright et al, 2006), and many researchers have concluded that dreams reflect waking-life stressors (e.g. Breger, 1967;Koulack, 1993;Piccioni et al, 2002;Schredl, 2002;Wright & Koulack, 1987).…”
mentioning
confidence: 99%
“…Many kinds of contemporary dream theories converge in their view that recurrent dreams are related to unresolved difficulties in the dreamer's life (e.g., Bonime, 1962;Domhoff, 1993;Fantz, 1987;Fosshage & Loew, 1987) and researchers have shown that the occurrence of recurrent dreams during adulthood is associated with stressors and lowered levels of psychological well-being (Brown & Donderi, 1986;Cartwright, Lloyd, Knight, & Trenholme, 1984;Robbins & Houshi, 1983;Zadra, O'Brien, & Donderi, 1998). Similarly, one study of 11-year-old children found that the presence of recurrent dreams was associated with emotional difficulties in boys although not necessarily in girls (Gauchat, Zadra, Tremblay, Zelazo, & Seguin, 2009).…”
Section: Introductionmentioning
confidence: 99%